Potential Moderators of Racial Differences in Responses to Traumatic Events. Issue 3 (3rd April 2017) - Despeaux, Katie E.; Jahn, Danielle R.
ABSTRACT: Research regarding the influence of race on outcomes after trauma has been mixed, and we aimed to identify potential moderators of the relation between race and posttraumatic stress disorder (PTSD)–related outcomes. We conducted a secondary analysis of data from 477 participants in the Collaborative Psychiatric Epidemiology Surveys. African American individuals reported a shorter duration of and less frequent PTSD symptoms than Caucasian individuals, and also endorsed a greater number of reexperiencing and avoidance symptoms. Education, socioeconomic status, and social support did not significantly moderate relations between age of worst trauma and PTSD-related outcomes. Clinical and research implications are discussed.